2011
DOI: 10.1097/fjc.0b013e31821533cc
|View full text |Cite
|
Sign up to set email alerts
|

Short-term Aerobic Exercise Reduces Nitroglycerin-induced Orthostatic Intolerance in Older Adults With Type 2 Diabetes

Abstract: Aims/Hypothesis-Older adults are at a high risk for syncope due to orthostatic intolerance (OI), and this risk increases with comorbid type 2 diabetes and vasoactive medications. Despite many benefits, previous investigations have shown worsening OI with aerobic training. We examined whether aerobic exercise reduced OI in older adults with type 2 diabetes who were given a short-acting vasoactive agent (nitroglycerin).Methods-Forty older adults (25 males and 15 females, mean age 71.4 ± 0.7 years, ranging in age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Fifteen articles showed unclear risk of bias [37–39, 41, 42, 47, 50, 55, 57, 58 63–65, 67, 68] and six showed high risk of bias [ 40 , 51 , 52 , 61 , 62 , 66 ] in adequate allocation concealment. Blinded outcome assessment was reported in 10 studies [ 39 , 44 47 , 49 , 53 , 59 , 60 , 69 ]. In terms of incomplete outcome data, four studies were judged as high risk [ 36 , 54 , 66 , 69 ] and three were unclear risk [ 35 , 43 , 48 , 67 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fifteen articles showed unclear risk of bias [37–39, 41, 42, 47, 50, 55, 57, 58 63–65, 67, 68] and six showed high risk of bias [ 40 , 51 , 52 , 61 , 62 , 66 ] in adequate allocation concealment. Blinded outcome assessment was reported in 10 studies [ 39 , 44 47 , 49 , 53 , 59 , 60 , 69 ]. In terms of incomplete outcome data, four studies were judged as high risk [ 36 , 54 , 66 , 69 ] and three were unclear risk [ 35 , 43 , 48 , 67 ].…”
Section: Resultsmentioning
confidence: 99%
“…In terms of incomplete outcome data, four studies were judged as high risk [ 36 , 54 , 66 , 69 ] and three were unclear risk [ 35 , 43 , 48 , 67 ]. Eleven studies showed unclear risk of bias in selective reporting [ 34 , 35 , 40 , 41 , 45 , 47 , 50 , 53 , 59 , 60 , 66 ], and 16 showed unclear risks of other biases [ 38 , 42 , 44 , 45 , 47 , 48 , 50 , 55 , 57 , 59 , 60 , 62 , 63 , 65 , 67 , 69 ].…”
Section: Resultsmentioning
confidence: 99%
“…Aside from the obvious risk of falling in the elderly, orthostatic hypotension is associated with cardiovascular mortality and all-cause mortality [ 124 ]. Orthostatic tolerance decreases with both age and diabetes [ 125 128 ].…”
Section: Orthostatic Tolerancementioning
confidence: 99%
“…There are a number of different neuroautonomic etiologies for syncope in older adults, including orthostatic hypotension, vasovagal syncope, postprandial hypotension and carotid sinus syndrome (the focus of the current study). Aerobic exercise has been shown to be beneficial in young adults with orthostatic hypotension [19], and aerobic training improves tilt table tolerance in older adults [20]. Aerobic exercise has been shown to give some limited benefits in older adults with postprandial hypotension [21], but has shown no benefit in preventing vasovagal syncope during laboratory conditions [22].…”
Section: Discussionmentioning
confidence: 99%